The Computer and Guidance in the United States Past, Present, and a Possible Future - Harris, Jo Ann.; Tiedeman, David V.; ERIC Clearinghouse on Adult, Career, and Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
In presenting the state of the art of the computer in guidance programs, it is maintained that there are many potential uses for computers in career decision making. Four types of computer-involved guidance systems were in use in 1970: indirect inquiry systems, direct inquiry systems without system monitoring, direct inquiry with system monitoring, and direct inquiry with system and personal monitoring. Of the 25 to 30 systems existing then, only five remain. They are direct inquiry systems, and all but one are directed to secondary school students. They are cost feasible, use standard terminal equipment, and specialize in providing career decision making information, retrieval, sorting, and synthesis. DISCOVER is the newest computer-based guidance system under development in the United States. It differs from other systems in objectives, functions, and population. Further developments in the field are anticipated involving self-initiated, self-directing, self-correcting learning, based on the theory that only each man can help himself. (AG)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
ERIC Note: A paper prepared for the Symposium on Computer-Based Counseling, 18th Congress, International Association of Applied Psychology (Montreal, Quebec, July 31, 1974).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Choice; Career Counseling; Computer Oriented Programs; Decision Making; Secondary School Students; Success; Computerized Vocational Information System -- Information System for Vocational Decisions; Speeches/Meeting Papers